Identifying patients with depression in primary healthcare - Jankowska, Paula; Jankowski, Krzysztof; Rudnicka-Drożak, Ewa (Journal of Education, Health and Sport, 2018)
IntroductionIt is estimated that in 2015 in Poland 1 878 988 patients suffered from depression. Depressive disorder is associated with significant decrease of life quality. Untreated depression can be fatal, as it is a recognized risk factor for a suicide attempt. Thus, identification of patients with symptoms of depressive disorder in primary healthcare is very important, as rapid implementation of treatment can prevent unfavorable depression effects. ObjectiveThe aim of this study is to present ways of identification patients with depressive disorder and screening tools suitable for primary healthcare setting. ResultsCareful physical examination and history taking are highly important in depresion case finding. Patients may present with many uncharacteristic somatic complaints. Moreover, there are some group of patients that are at higher risk of depressive disorder. The most important one includes patients with other mental disorders; previous history of depression and familial predisposition to depression. There are many depression screening tools. The most popular are Patient Health Questionnaire, Beck Depression Inventory and Geriatric Depression Scale.ConclusionsMany individuals, finally diagnosed with depressive disorder, meet their family doctor for uncharacteristic complaints. This is highly important for primary care physicians to be acquainted with most common somatic manifestations of depression. In primary care setting PHQ-2, PHQ-9 can be successfully used. BDI-PC also appears as measure suitable for family physicians. Geriatric population should be assessed with use of shorter version of GDS, but PHQ-2, and PHQ-9 are also recommended for this age group.